PENDIDIKAN KESEHATAN FAKTOR PENYEBAB STUNTING - Sri Handayani; Yopi Suryatim Pratiwi; Yadul Ulya; Siskha Maya Herlina; Nurul Fatmawati (Jurnal LENTERA, 2022)
Stunting is a short and very short body condition that exceeds the deficit of -2 SD belowthe median length or height. Stunting can be diagnosed through the anthropometricindex of height for age which reflects the linear growth achieved in pre and post deliverywith an indication of long-term malnutrition, resulting from inadequate nutrition.Indonesia is still high and is a health problem that must be addressed. Indonesia is in the5th highest rank with the prevalence of stunting children. After India, China, Nigeria andPakistan. The prevalence of stunting in NTB Province is 37.2%, higher than the nationalaverage of 29.6%. That number also increased when compared with the year. 2016which amounted to 29.9% or an increase of 7.29%. For the highest prevalence of stuntingin Sumbawa Regency, namely 41.9% followed by Central Lombok 39.9%, Dompu 38.3%,Mataram City 37.8%, North Lombok 37.6%, Bima 36.6%, Bima City 36 , 3%, West Lombok36.1% and East Lombok 35.1%. Stunting is a linear growth that fails to reach its geneticpotential as a result of poor diet and infectious diseases. In this service activity themethod used is health education about the causes of stunting. Health educationactivities on the factors causing stunting as an effort to increase knowledge of thefactors causing stunting, which were carried out in Geguntur Village, Sekarbela District,Mataram City on May 30, 2022, were attended by 35 mothers. The results of theparticipants' pretest and posttest showed an increase in knowledge about healtheducation on the factors that cause stunting. After this community service activity, it ishoped that the mother's attitude is also positive regarding the factors that causestunting and can apply it in daily life so that stunting events can be prevented early.